Studi Literatur Penggunaan Media Wordwall Terhadap Hasil Belajar Siswa pada Pembelajaran IPS - Shasi Jannah Arnanda; Desy Safitri; Sujarwo (Indo-MathEdu Intellectuals Journal, 2026)
The low level of student engagement and learning outcomes in social studies learning has prompted the need for the use of interactive and effective digital learning media. This study aims to analyze the use of Wordwall media on student learning outcomes in social studies learning through a literature review. The study used a literature review method with a descriptive qualitative approach. Data sources were obtained from various scientific articles accessed through academic databases such as Google Scholar, Garuda, and indexed national and international journals. The selection process was carried out using inclusion and exclusion criteria, resulting in 20 relevant articles, consisting of 17 core articles on Wordwall and 3 supporting articles on digital media for social studies learning. Data were analyzed using content analysis techniques. The results of the study indicate that the use of Wordwall media generally has a positive impact on social studies learning, characterized by increased learning outcomes, motivation, engagement, and student participation during the learning process. In addition, Wordwall has advantages in the form of interactivity, gamification elements, flexibility of use, and ease of implementation in various learning contexts. Thus, Wordwall can be an alternative, effective digital learning media in supporting the improvement of student learning outcomes in social studies learning.